Civic engagement through restaurant review page in Facebook: a structural equation modelling approach. Issue 2 (18th January 2021) - Satter, A.K.M. Zaidi; Mahmud, Arif; Rahman, Ashikur; Mahmud, Imran; Akter, Rozina
Abstract : Purpose: Existing literature affirms that almost half of the young generation has remained unemployed worldwide. On the contrary civic engagement can be a powerful tool in combating this problem. However, the influencing factors that encourage the active participation of young adults yet to be identified. The purpose of this paper is to fill the research gap by creating and validating a research model by including three motives social presence commitment and online offline civic engagement. Design/methodology/approach: The study took a quantitative approach to conduct a cross-sectional study. In total, 214 data were collected from the member of a Facebook group of Bangladesh named Foodbank, a restaurant review page through the online questionnaire. After that structural equation modelling techniques have been used to analyse the data, test the model validity and hypothesis. Findings: The result shows that both commitment and social presence influence offline and online civic engagement. Excitement motives have a higher effect than information and convenience motive. Besides, 8 out of 10 hypotheses have shown significant results, with only the convenience motive not having any positive influence and effect on social presence and commitment. Practical implications: Almost 47.6 out of 158.5 million are young people who are incapable of contributing fully to national development due to a lack of civic engagement. The outcome of this study will be useful for the Government of Bangladesh, as well as for non-governmental organisations and decision-making authorities to form assessments and develop policy on how to engage the young generation in civic activities to achieve further socio-economic development in the country. Originality/value: This study contributes to existing literature with newly developed relationships between social presence-civic engagement and commitment-civic engagement. These unique relationships have been empirically tested and resulted insignificant. The study also identifies that it is vital to engage young people more in social works and increase their participation in offline and online activities.